Generalized Fuzzy Quasi-Ideals of an Intraregular Abel-Grassmann's Groupoid. (31st May 2012) - Davvaz, Bijan; Khan, Madad; Anis, Saima; Haq, Shamsul
Abstract : We have introduced a new nonassociative class of Abel-Grassmann's groupoid, namely, intraregular and characterized it in terms of its( ∈, ∈ ∨ q ) -fuzzy quasi-ideals.